Evaluation of Road Traffic Accidents (RTAs) on Hyderabad Karachi M-9 Motorway Section - Detho, A.; Samo, S. R.; Mukwana, K. C.; Samo, K. A.; Siyal, A. A. (Engineering, Technology & Applied Science Research, 2018)
Pakistan is a developing country and its development depends upon its transports facilities. This paper describes the findings of a survey for the evaluation of road traffic accidents (RTAs) that focused on the Hyderabad-Karachi M-9 Motorway section. The objectives of the survey are the collection the data of traffic accidents including the human and property losses and the evaluation of RTAs causes. During a two year period (i.e. 2015 and 2016) it was revealed that 145 RTAs occurred on the motorway. In those RTAs, 109 persons died and 293 got injured and 251 vehicles were damaged. High risk percentages were recorded for both pedestrian and vehicle users.